Evaluating the Efficiency of University Services at the University of Wasit in Light of Sustainable Development Goals: An Analytical Study of Academic, Administrative, and Infrastructure Services - Dr. Lama Abd Almanaf Rahim; Dr.ALI LAFTA SAEED; Dr. Ameera Muhammad Ali Hamza; Assis.Lectu. Noha Majeed Hamid (Journal of College of Education, 2025)
This study aims to evaluate the efficiency of university services at the University of Wasit based on sustainable development standards, with a focus on academic and administrative services as well as infrastructure. It seeks to identify areas that require development to ensure the sustainability and quality of the educational process. The research adopted a descriptive, inductive, and quantitative analytical approach, utilizing surveys and interviews with university faculty members, administrative staff, and students. A randomly selected sample of 1,537 participants was used to ensure proper representation.Descriptive statistics and data analysis tools (SPSS and Excel) were employed to analyze responses to ten key indicators, using statistical analysis (factor analysis) to highlight the significance of university service efficiency in achieving sustainable development. The study provides insights that can help formulate sustainable development policies aimed at enhancing education quality and the university environment at the University of Wasit in the long term.The findings indicate a high awareness rate of sustainable development goals, with 98.1% of respondents engaging in scientific activities that promote environmental sustainability. However, the lowest availability rate was recorded for healthcare services, at only 44.8% of respondents. The results of factor analysis, which examined correlation coefficients to diagnose the key determinants of the relationships among the studied indicators, suggest that the University of Wasit has a strong foundation for achieving sustainability in its university services. However, certain challenges need to be addressed, particularly in improving infrastructure, updating curricula, and expanding healthcare and digital services.                                   The study recommends enhancing the university’s healthcare services by establishing a teaching hospital, promoting the use of clean energy sources in university buildings, and prioritizing scientific research and innovation.
Keywords: Sustainable Development , Quality of Education, Service Efficiency